(untitled) (Research, Society and Development, 2024)
Depression is currently considered the evil of the century, there are several factors and mechanisms for the development, maintenance and progression of this chronic psychiatric disease. Due to its exponential growth in recent years, especially after the COVID 19 pandemic, there has been a significant increase in the studies and formulation of new pharmacological and non-pharmacological techniques and skills for coping with depression, as is the case with the promotion of physical activity as preventive and therapeutic way. Therefore, the present study aimed to investigate the benefits of regular physical activity in the treatment of individuals diagnosed with depression. As a methodological approach, a narrative literature review was carried out, searching the Scielo, Pubmed and Virtual Health Library databases, 12 articles were selected in English and Portuguese in the last 5 years, from 2020 to 2024. In conclusion, physical activity demonstrates a range of benefits for individuals dealing with depression. In addition to the direct effects on neurotransmitters associated with mood, such as serotonin, dopamine and norepinephrine, exercise also stimulates neurogenesis in the hippocampus, the part of the brain responsible for emotional processing, promotes improved sleep by regulating the sleep-wake cycle, reduces isolation and improves social well-being as it provides engagement and a sense of belonging.